1968
DOI: 10.1507/endocrj1954.15.247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age and Thyrocalcitonin on Myocardial Changes Induced by Sodium Sulfaacetylthiazole

Abstract: SYNOPSISNa-sulfaacetylthiazole, 0.5g/kg body weight, was injected into immature and adult rats to produce obstructive nephropathy. Necrotic changes in the myocardium were found in all of the 9 adult rats of about 120days of age, whereas no such changes occured in immature animals of about 40days of age. Thyrocalcitonin, 50 mMRC units a day injected subcutaneously for one week, completely inhibited the occurrence of such myocardial lesion in adult animals, as did parathyroidectomy performed one week previously.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1970
1970
1996
1996

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The effect of parathyroidectomy in preventing these SAT‐induced cardiovascular changes has been demonstrated histologically by Lehr (1), who pointed out the importance of age and calcium metabolism in the development of such lesions. Fujita et al (2) in 1968 showed histologically the preventive effect of age and thyrocalcitonin in addition to that of parathyroidectomy, with respect to these SAT‐induced cardiovascular changes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The effect of parathyroidectomy in preventing these SAT‐induced cardiovascular changes has been demonstrated histologically by Lehr (1), who pointed out the importance of age and calcium metabolism in the development of such lesions. Fujita et al (2) in 1968 showed histologically the preventive effect of age and thyrocalcitonin in addition to that of parathyroidectomy, with respect to these SAT‐induced cardiovascular changes.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the definite preventive effect of parathyroidectomy on SAT‐induced cardiovascular changes, thyrocalcitonin may be expected to antagonize the action of parathyroid hormone by inhibiting bone resorption which might be followed by metastatic calcification. Fujita et al (2) reported that 50 mrc mu of thyrocalcitonin was effective for the prevention of SAT‐induced cardiovascular changes, based on histological study. In our series, however, daily administration of 200 mrc mu of thyrocalcitonin prevented only the increase of calcium in the heart, and had no preventive effect on the accumulation of 45 Ca in soft tissues or on arterial calcification and myocarditis in SAT‐treated adult animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations